Storm time ionosphere and plasmasphere structuring: SAMI3‐RCM simulation of the 31 March 2001 geomagnetic storm. Issue 23 (9th December 2014) - Huba, J. D.; Sazykin, S.
Abstract: We present the first self‐consistent modeling study of the ionosphere‐plasmasphere system response to a geomagnetic storm. We use the coupled SAMI3‐Rice Convention Model (RCM) of the global ionosphere and inner magnetosphere, with self‐consistent electrodynamics, to simulate the 31 March 2001 magnetic storm. We find that the penetration electric fields associated with the magnetic storm lead to a storm time‐enhanced density (SED) in the low‐ to middle‐latitude ionosphere and that the separation in latitude of the Appleton anomaly peaks increases. The SED exhibits magnetic conjugacy, occurring in both the Northern and Southern Hemispheres. Moreover, mapping the boundary of the SED into the equatorial plane coincides with the development of a "plume‐like" structure in the plasmasphere. These preliminary results are consistent with observations. Key Points: First self‐consistent model of storm time ionosphere/ plasmasphere dynamics First model demonstrating connection of SED with plasmasphere plumes First model showing connection of TEC enhancements from middle‐ to high‐latitude